Combination of mechanical and chemical extraction of astaxanthin from Haematococcus pluvialis and its properties of microencapsulation - Pan-utai, Wanida; Boonpok, Sirinapa; Pornpukdeewattana, Soisuda (My University, 2021)
Astaxanthin is a red pigment that is naturally produced by the freshwater microalga Haematococcus pluvialis. Cell wall thickness of red cyst aplanospores is a barrier for extraction. Astaxanthin extraction from H. pluvialis UTEX 2505 was improved by ultrasonic assistance techniques with various conditions of solvent, extraction time and cycles of extraction to generate maximum recovery. Highest astaxanthin content and extraction yield were obtained using ethyl acetate under ultrasonic treatment for 25 min with five repeated extraction cycles. Encapsulation of astaxanthin was studied at different conditions. Ratio of maltodextrin and gum Arabic at 7.5:2.5 was most suitable for astaxanthin microencapsulation. Increased encapsulation efficiency of astaxanthin powder is suitable for food, pharmaceutical and other natural astaxanthin applications from H. pluvialis.
Keywords: Astaxanthin; Encapsulation; Extraction; Haematococcus; Properties